دراسة تقويمية لكتاب تعليم اللغة العربية للناطقين بغيرها : من وجهة نظر المعلمين والطلاب - فكي، محمد الطيب إبراهيم (Ma'ahad al-Tarbiyah, al-Jami'ah al-Islamiyah al-'Alamiyah Maliziya, 2011)
The purpose of this study is to contribute to the enhancement of Arabic course textbook to non-Arabic speakers in general and to the innovation of the three volumes of Arabic series for non-Arabic speakers, 'Silsilah Ta'lim al-'Arabiyyah li ghairi al-natiqina biha' The Essential Arabic book, which are offered by Qur'anic Language Division (QLD), CELPAD) since 2002. Both methods of qualitative but mainly quantitative have been employed in the study. The data were processed by SPSS Windows and crossed examined with the qualitative output by citing interview excerpts. It has been concluded from teachers and students opinions that the current series is just acceptable and doesn't fully satisfy the foundations and descriptors of the course textbook of Arabic to non-Arabic speakers. Consequently the researcher recommends continuing the adoption of the series by QLD temporarily after a thorough revision of its weaknesses. On the other hand he proposes writing a new four volumes of series to fulfill the needed requirement. He also encourages CELPAD to adopt sound methods for evaluating or choosing Arabic textbooks. Finally he suggests that the instrument developed for the current study to be adapted and utilized in conducting future studies on advanced levels of Arabic textbooks.